2007
DOI: 10.1111/j.1365-2249.2007.03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonality analysis of lymphoproliferative disorders in patients with Sjögren's syndrome

Abstract: SummaryThe aim of this study was to clarify the nature of the clonal lymphocyte infiltration in Sjögren's syndrome (SS) patients associated with lymphoproliferative disorders. We examined B cell clonality in lymphoproliferative tissues from six primary SS patients associated with lymphoproliferative disorders or lymphoma by cloning and sequencing of the gene rearrangement of the immunoglobulin heavy chain complementarity determining region 3 (IgVH-CDR3). Three patients with sequential observation showed progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…The other three SS patients concomitant with malignant B cells lymphomas showed different clonal expansion of B cells between nodal sites and salivary glands [62]. Similar cases were also observed in our study [62]. Forty-two patients showed evidence of monoclonal B cell expansion by PCR.…”
Section: Clonality Analysis In Lymphoma Devel-opmentsupporting
confidence: 88%
“…The other three SS patients concomitant with malignant B cells lymphomas showed different clonal expansion of B cells between nodal sites and salivary glands [62]. Similar cases were also observed in our study [62]. Forty-two patients showed evidence of monoclonal B cell expansion by PCR.…”
Section: Clonality Analysis In Lymphoma Devel-opmentsupporting
confidence: 88%
“…In contrast, other studies showed that the detection of monoclonality by immunoglobulin gene rearrangement was not a reliable predictor of clinical behavior in MESA, inasmuch as initial and follow-up biopsy specimens from the same patients were identical [96]. Similar findings were observed in our study [98]. Thus, molecular genetic analysis of monoclonality has little practical value in the clinical diagnosis of salivary gland lymphoma in MESA, and these patients should be diligently followed-up for evidence of lymphoma development [104].…”
Section: Clonality Analysis In Lymphoma Developmentsupporting
confidence: 81%
“…Three longitudinally observed patients showed progressive clonal expansion with the presence of the same subclone in different tissues during the course of disease, with one developing MALT lymphoma in the parotid gland. The other three SS patients had malignant B cells between nodal sites and salivary glands [98]. Table 1 summarizes findings regarding monoclonality and lymphoma development in 45 patients with SS.…”
Section: Clonality Analysis In Lymphoma Developmentmentioning
confidence: 99%
“…In fact, a large number of SS patients develop B cell non‐Hodgkin's lymphoma (NHL), associated mainly with mucosa‐associated lymphoid tissue (MALT) lymphomas of primary gland origin, according to a concept introduced by Dong et al. [5], Tonami et al. [7] and Isaacson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Infiltrated glands are frequently the site of B cell oligoclonal and monoclonal expansion, an undesirable condition leading to lymphoid malignancy in >14% of SS cases [5,6]. In fact, a large number of SS patients develop B cell non-Hodgkin's lymphoma (NHL), associated mainly with mucosa-associated lymphoid tissue (MALT) lymphomas of primary gland origin, according to a concept introduced by Dong et al [5], Tonami et al [7] and Isaacson et al [8]. Elevated serum levels of BAFF have been also found in patients with NHL [9].…”
Section: Introductionmentioning
confidence: 99%